The simulacrum in contemporary science fiction: Atwood, Willis, Piercy, Collins, Cadigan - Amanda Pavani Fernandes (2020)
This dissertation investigates five science fiction novels, published between 1991 and 2015, and their relationship with senses of reality, communication, mediation of experiences, the industry of entertainment, of political propaganda and the complex ties between humanity and technology. The analysis based on Jean Baudrillard’s concept from Simulacra and Simulation (1992), the simulacrum, formed of “copies that depict things that either had no original, or that no longer have an original”. The literary works analysed were: Connie Willis’ The Doomsday Book (1992); Margaret Atwood’s Oryx and Crake; Margaret Atwood’s The Heart Goes Last; Marge Piercy’s He, She, and It (1993); Pat Cadigan’s Synners (1991); and Suzanne Collins’ Mockingjay (2013). The research included a discussion of the critical trajectory of Baudrillard’s views on copies, originals, and symbols, in relation to his political history and his connections to both Marxist and, later, Postmodernist values, after which a claim is made on the relevance of reading literature through the simulacrum as an intra-medial approach, that is, by analysing instances of novels as opposed to seeing literature as a simulacrum itself. Oryx and Crake is related to simulacra in the way it depicts a rupture with processes of signification, with a conquest of the arts and most forms of entertainment through the simulacrum. The concept is also studied from the perspective of Utopian Studies: based on Tom Moylan’s critical work, traces in common between science fiction, utopianisms and their world-building practices are outlined and exemplified in the utopian/dystopian moving blocks of The Doomsday Book, which subverts stereotypes of the future as necessarily advanced in contrast to the supposedly regressive Middle Ages. The Heart Goes Last is structured around a dystopia within an abstract utopia, to use Ernst Bloch’s terminology; it warps experiences in its reduction of art and media from company-sanctioned movies from the 1950s and other pieces deemed harmless and pleasant. He, She, and It includes a utopian enclave, the small town of Tikva, in a context that includes the substitution of nations for conglomerates. Their survival commodity is simulations, chimeras, programming pieces. Terry Eagleton’s analysis of the role ideology plays in literature is also discussed and compared to the functioning of simulacra, and their appearances in the novels in relation to a naturalization of hegemonic discourses. That is the case in Cadigan’s Synners, whose world deteriorates as a result of unchecked capitalism and progress for its own sake. In Mockingjay, by Collins, that ideology is that of war propaganda, which fabricates narratives to justify state violence and validate pre-existing powers. The narrative in contemporary science fiction is often interconnected by simulacra, whose perception can foster critical readings and a displacement of certainties, which would enrich the reading experience.